Lost Confidence and Human Capability: A Hermeneutic Phenomenology of the Gendered, yet Capable Subject - Anderson, Pamela Sue (Text Matters: A Journal of Literature, Theory and Culture, 2014)
In this contribution to Text Matters, I would like to introduce gender into my feminist response to Paul Ricoeur’s hermeneutic phenomenology of the capable subject. The aim is to make, phenomenologically speaking, “visible” the gendering of this subject in a hermeneutic problematic: that of a subject’s loss of confidence in her own ability to understand herself. Ricoeurian hermeneutics enables us to elucidate the generally hidden dimensions in a phenomenology of lost self-confidence; Ricoeur describes capability as “originally given” to each lived body; but then, something has happened, gone wrong or been concealed in one’s loss of confidence. Ricoeur himself does not ask how the gender or sex of one’s own body affects this loss. So I draw on contemporary feminist debates about the phenomenology of the body, as well as Julia Kristeva’s hermeneutics of the Antigone figure, in order to demonstrate how women might reconfigure the epistemic limits of human capability, revealing themselves as “a horizon” of the political order, for better or worse.